Methyl 4-[N-(5-bromopyrimidin-2-yl)carbamoyl]benzoate - Hu, Hui-Ling (International Union of Crystallography, 2012)
In the title compound, C(13)H(10)BrN(3)O(3), the pyrimidine and benzene rings are twisted with an interplanar angle of 58.4 (1)°. The secondary amide group adopts a cis conformation with an H—N—C—O torsion angle of 14.8 (1)°. In the crystal, molecules are connected into inversion dimers via pairs of N—H⋯N hydrogen bonds, generating an R (2) (2)(8) motif. The dimers are further connected through a C—Br⋯O interaction [3.136 (1) Å and 169.31 (1)°] into a chain along [110]. Weak C—H⋯N hydrogen bonds between the methyl benzoate groups and pyrimidine rings are also observed in the crystal structure.